2016
DOI: 10.21037/qims.2016.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of left ventricular “rigid body rotation” during dipyridamole-induced stress in a patient with stable angina: a case from the three-dimensional speckle tracking echocardiographic MAGYAR-Stress Study

Abstract: Abstract:The left ventricular (LV) twist is defined as the wringing motion of the heart around its longaxis in systole caused by oppositely directed counterclockwise apical and clockwise basal rotations resulted from the movement of two orthogonally oriented muscular bands. In some clinical circumstances, rotation at both basal and apical levels of the LV occurred in the same clockwise or counterclockwise direction during systole resulting the near absence of LV twist as called left ventricular "rigid body rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Peteiro et al found that LV torsion decreased with ischemia due to worsening of basal rotation in CAD patients, whereas LV apical rotation was not impaired, suggesting the existence of an apical compensatory mechanism . In a recent case report, reversal of LV‐RBR could be detected in a patient without significant CAD during dipyridamole‐induced stress in which basal LV rotation became normally clockwise oriented at peak hyperemia, but returned to LV‐RBR at the recovery phase …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Peteiro et al found that LV torsion decreased with ischemia due to worsening of basal rotation in CAD patients, whereas LV apical rotation was not impaired, suggesting the existence of an apical compensatory mechanism . In a recent case report, reversal of LV‐RBR could be detected in a patient without significant CAD during dipyridamole‐induced stress in which basal LV rotation became normally clockwise oriented at peak hyperemia, but returned to LV‐RBR at the recovery phase …”
Section: Discussionmentioning
confidence: 97%
“…3 In a recent case report, reversal of LV-RBR could be detected in a patient without significant CAD during dipyridamole-induced stress in which basal LV rotation became normally clockwise oriented at peak hyperemia, but returned to LV-RBR at the recovery phase. 8 3DSTE is a new noninvasive clinical tool with the ability to create a three-dimensional model of the LV and atria along the cardiac cycle. Over accurate volumetric measurements, 9,10 uni-and multidirectional strains and parameters characterizing LV rotational mechanics can be calculated at the same time from the same digitally acquired three-dimensional datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some reports found LV-RBR in congenital heart diseases and in infiltrative disorders such as cardiac amyloidosis. [78] In a case report, a pair of identical twins was presented to have LV-RBR (clockwise and counterclockwise), the twins had twin-to-twin transfusion syndrome in the past medical history. [9] In addition to these results, two reports have found reversal of LV-RBR.…”
Section: Discussionmentioning
confidence: 99%
“…Following the recovery phase of the stress protocol, all these changes in rotational mechanics returned back to LV-RBR. [8]…”
Section: Discussionmentioning
confidence: 99%
“…38 New initial experiences with 3D-derived STE highlight the potential usefulness of this technique during stress echo, in both animals and humans. 39,40 However, this kind of application is still far from being of current clinical practice.…”
Section: A B C Dmentioning
confidence: 99%